Justification of criminal procedure decisions as an element of the principle of legality - Abzalbekova, M.T. (KSU publ., 2019)
Decision-making is one of stages in development of purposeful activity. It is known that in the course of investigation there is a movement from incomplete, possible knowledge to knowledge proved, reliable. The need to adopt this or that decision on case is depending on a stage of investigation and is caused by character and contents of information which a certain official has by this time, competent to make the relevant proceeding decisions. Validity of criminal procedure decisions is one of the most important problems of criminal proceedings. The validity of criminal procedure decisions means that given decisions corresponds to the actual circumstances of criminal case have taken place in fact. The identity of decision-making in criminal proceedings consists that possible means of achievement of the goals are specified in the law, but are not elected randomly by the person, given the right to make the decision. Considering a problem of validity of proceeding decisions, it is impossible to ignore the decisions reasons concept of criminal proceedings as the decision is considered reasonable in the presence of all bases necessary for its acceptance. The purpose of article is identification of signs of a concept of criminal procedure decisions justifications. According to the purpose the following tasks are set: to carry out the analysis of a concept of proceeding decisions, consideration of validity as element of the legality principle.The methodological basis of the study is a systematic, formal-legal, research methods in combination with a comprehensive analysis of the issues studied. As a result of a research the category of decisions validity is analyzed, the proceeding decision validity assumes the existence of sufficient proofs to establish the actual facts of the case, the validity of criminal procedure decisions is important component of the legality principle in criminal proceedings and the rights for fair judicial proceedings.
Keywords: proceedings; problems of criminal proceedings; the principle of legality; the decision in criminal proceedings; a sentence; justification of the criminal procedure decision; motivation; legality of decisions; requirements imposed to the decision; regularity of the criminal procedure decision